Comparison of Physico–Chemical and Sensory Characteristics of Pawpaw Juice Extracted with Locally Produced and Commercial Pectin Enzymes (Journal of Science and Technology, 2016)
Fruit juices are often extracted more efficiently (faster rate of extraction or higher yield) by the application of pectin enzymes which are commercially available. A survey of small scale juice processors in Ghana indicated low level of production due to inefficient methods of extraction. These processors could therefore benefit from use of pectin enzymes in their operation. Our laboratory has been investigating the activity of pectin enzymes produced locally from Saccharomyces cerevisiae (ATCC 52712) in fruit juice processing. In this report, pawpaw juice was extracted with the Saccharomyces cerevisiae enzyme as well as a commercial pectin enzyme, Rohapect D5L under previously determined optimum conditions. The characteristics of the juices were then compared in order to evaluate the usefulness of the locally produced yeast enzyme to the local fruit juice industry. Fixed quantities of the yeast and commercial enzymes were added to a known amount of papaya mash and the samples held at room temperature for 30 minutes after which the samples were filtered to obtain the juice. Sensory analysis as well as physical and chemical properties of the juices were then determined on each sample. Physico – chemical characteristics of pawpaw juice such as pH, titrable acidity and color were not different when compared to control or the commercial enzyme extracted juice. Similarly, important sensory characteristics of the juice such as aroma, color, taste, cloudiness and acceptability were also comparable to that of the control and those extracted with the commercial enzyme. The results indicate the possibility of using locally produced pectin enzymes for fruit juice extraction. The potential applicability of the method to the industry is being evaluated in a scale – up extraction process.